Rattle-type magnetic mesoporous hollow carbon as a high-performance and reusable adsorbent for water treatment. (January 2017) - Kalantari, Mohammad; Yu, Meihua; Noonan, Owen; Song, Hao; Xu, Chun; Huang, Xiaodan; Xiang, Feixiang; Wang, Xiaolin; Yu, Chengzhong
Abstract: Rattle-type magnetic mesoporous hollow carbon (RMMHC) materials have shown great promise as adsorbents for water treatment. In this work, we report a surfactant-free synthesis of RMMHC nanoparticles (NPs) using magnetite NPs as the core, tetrapropyl orthosilicate, resorcinol and formaldehyde to form the shell followed by carbonization and selective silica etching. The pore size, specific surface area and pore volume of RMMHC NPs can be tuned by varying the carbonization temperature (500, 700 and 900 °C). At the optimized temperature of 700 °C, the RMMHC NPs possess the highest specific surface area of 579 m 2  g −1, the largest pore volume of 0.795 cm 3  g −1, and the largest pore size of 7.6 nm among all three samples. The adsorption capacity of optimized RMMHC NPs towards di (2-ethylhexyl) phthalate (a model organic pollutant) reaches as high as 783.1 mg g −1 . Taking advantage of the magnetic property, the adsorbents retain more than 87% of their initial adsorption capacity over five times' reuse. Graphical abstract: Highlights: Synthesis of large pore size rattle-type magnetic mesoporous hollow carbon nanoparticles (RMMHC NPs). A new understanding of the influence of carbonization temperature on the properties of RMMHC NPs. A superior performance for water treatment.